Optimalisasi Pencatatan Penjualan Pupuk Berbasis UI/UX Dengan Pendekatan HCD Untuk Meningkatkan Efisiensi Pemantauan Usaha - Rahel Lady Dear Purba; Unang Rio; Karpen; Fransiskus Zoromi (PPPM Institut Teknologi Pagar Alam, 2025)
Padamu Jaya Bersama is a company engaged in the sale of oil palm fertilizer and currently relies on manual transaction recording. This approach leads to various challenges, such as the risk of data loss, delays in information access, and inefficiencies in business monitoring processes. This study aims to address these issues by designing a digital recording system based on a Progressive Web App (PWA) optimized through the Human-Centered Design (HCD) approach. The HCD method is applied through the stages of inspiration, ideation, implementation, and testing, involving business owners and employees as the primary users. The interface design is created using low-fidelity wireframes developed with the Balsamiq tool to illustrate the basic structure and navigation flow of the system. The application is developed using HTML, PHP, CSS, and JavaScript technologies, featuring key functions such as sales recording, stock management, and report generation. Testing results indicate that the designed system improves recording efficiency, accelerates access to sales data, and facilitates business monitoring for the owner. This study concludes that the HCD approach is effective in producing a system that meets user needs.